IMPLEMENTASI PEMBELAJARAN EKOSISTEM MELALUI PENDEKATAN SAINTIFIK DENGAN MODEL DISCOVERY LEARNING MATA PELAJARAN IPA KELAS V - SUBIYATMI SUBIYATMI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The research was motivated by the problem of low student learning outcomes, then through a scientific approach with the Discovery Learning learning model to improve the learning outcomes of fifth grade students at SDN Ciamis, North Sungkai District, North Lampung Regency. This research is a best practice activity consisting of two cycles, the stages of each cycle are planning, implementation, observation and reflection. The results of the analysis of student learning outcomes for class V SDN Ciamis North Sungkai District, North Lampung Regency in the first cycle of action were obtained from the number of students 26 students who took the test, there were 15 students or 57.69% who completed and 11 students or 42.30% declared not yet finished. With an average value of 67.30. Then the results of the analysis of student learning exams in cycle 2 were obtained from the number of students 26 students who took the test, there were 24 students or 92.30% who completed and 2 students or 7.69% were declared incomplete. With an average value of 83.46. Based on the results of the study, the researcher can conclude that through a scientific approach with the Discovey Learning learning model, learning Ecosystem science subjects for class V at SDN Ciamis can improve student learning outcomes. ABSTRAKPenelitian dilatar belakangi oleh permasalahan pada hasil belajar siswa rendah, maka melalui pendekatan santifik dengan model pembelajaran Discovery Learning untuk meningkatkan hasil belajar siswa kelas V SDN Ciamis Kecamatan Sungkai Utara Kabupaten Lampung Utara. Penelitian ini adalah kegiatan best practice yang terdiri dari dua siklus, tahapan setiap siklus adalah perencanaan, pelaksanaan, observasi dan refleksi. Hasil analisis ujian hasil belajar siswa kelas V SDN Ciamis Kecamatan Sungkai Utara Kabupaten Lampung Utara pada tindakan siklus 1 diperoleh dari jumlah siswa 26 siswa yang mengikuti tes, terdapat 15 siswa atau 57,69% yang tuntas serta 11 siswa atau 42,30% dinyatakan belum tuntas. Dengan nilai rata-rata 67,30. Kemudian pada hasil analisis ujian belajar siswa pada siklus 2 diperoleh dari jumlah siswa 26 siswa yang mengikuti tes, terdapat 24 siswa atau 92,30% yang tuntas serta 2 siswa atau 7,69% dinyatakan belum tuntas. Dengan nilai rata-rata 83,46. Berdasarkan hasil belajar peneliti dapat menyimpulkan bahwa melalui pendekatan saintifik dengan model pembelajara Discovey Learning pembelajaran Ekosistem mata pelajaran IPA kelas V di SDN Ciamis dapat meningkatkan hasil belajar siswa.